Case Report: Successful avoidance of etoposide for primary hemophagocytic lymphohistiocytosis-induced multiple organ dysfunction syndrome using emapalumab - Hahn, Timothy J.; McKeone, Daniel J.; Beal, James W.; Ericson, Jessica E.; Halstead, E. Scott (Frontiers in Pediatrics, 2024)
We describe the case of an infant who presented with simple rhinovirus/enterovirus bronchiolitis whose condition worsened with rapid progression to multiple organ dysfunction syndrome (MODS). The patient was presumed to have either primary or secondary hemophagocytic lymphohistiocytosis (HLH), and treatment was initiated using dexamethasone, anakinra, and intravenous immunoglobulin to modulate the immune system. Due to the organ dysfunction, the use of etoposide was avoided and instead, emapalumab, an interferon gamma antagonist, was administered at a dose of 6 mg/kg. The patient's organ failure improved, and the levels of inflammatory markers decreased. The flow cytometry analysis revealed that cytotoxic cells lacked perforin expression, and subsequent genetic analysis confirmed homozygous pathogenic mutations in the perforin gene. This case highlights the potential avoidance of etoposide in cases of primary HLH, the possible benefit of an elevated initial dose of emapalumab, and the contribution offered by a multi-specialty team approach to complex diagnosis.